Pengembangan Teacher Entrepreneur dalam Rangka Menciptakan peluang kerja bagi Mahasiswa dan lulusan S1 Pendidikan di Kabupaten Situbondo - Aenor Rofek (INTEGRITAS : Jurnal Pengabdian, 2017)
Students of FKIP UNARS graduates often complain about minimal job opportunities. The majority of FKIP graduates want to make the school as a place to live their profession but, because of the opportunity to become volunteer teachers (teachers), honorary teachers, non-permanent teachers, and civil servant teachers is very small, given the number of competitors, students FKIP UNARS graduates often complain about these opportunities . They are desperate not to have the opportunity to teach in formal institutions. Not only the lecture process, universities also need to think about the track record of the graduates. Based on the problems that are generally complained by students of FKIP UNARS graduates, equip them and assist them to establish independent business by utilizing the teaching skills acquired in college is the right solution. Therefore, in the process of equipping and assisting the establishment of independent business in the form of learning guidance institution will be conducted through a series of activities. The series of activities in community service are: Skill training which includes: Service management skill to study participants; The skill of managing a fund-friendly learning space; Communication skills and connecting for the sake of publication; Financial administration management skills; Skills to apply mastery learning in tutorial activities. The outcomes to be generated in this activity are 1) The growth of the spirit and the desire to build the self-guided learning institution, 2) The growth of skills in managing self-directed self-guidance institution, 3) The growth of the ability to provide service innovation to the learners for the sustainability of the guidance counseling institution , 4) The development of skills in mastery learning in teaching activities in the institution of learning guidance built, and 5) The development of communication skills in terms of publication self-help tutoring institutions.